2017
DOI: 10.4236/ajps.2017.812199
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Silver Nitrate in the In Vitro Development and Conservation of <i>Passiflora gibertii</i> N. E. Brown

Abstract: The aim of this study was to evaluate the effects of silver nitrate in the in vitro development and conservation of passion fruit plants. Experiments were carried out at the Laboratory of Culture and Tissues, in the National Cassava and Fruits Research Center (EMBRAPA), using microcuttings of Passiflora gibertii N. E. Br., previously cultivated in vitro. The microcuttings were placed in MS media supplemented with silver nitrate at concentrations of 0, 1, 2, 4 and 8 mg·L −1 , and, during 30, 60 and 90 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This is because after evaluation at 150 days of slow growth, many plants began to lose their leaves through the natural process of leaf abscission. In addition, passion fruit plants are known to produce higher concentrations of ethylene when grown in vitro (Trevisan & Mendes, 2005;Faria et al, 2017). Ethylene is a Acta Scientiarum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because after evaluation at 150 days of slow growth, many plants began to lose their leaves through the natural process of leaf abscission. In addition, passion fruit plants are known to produce higher concentrations of ethylene when grown in vitro (Trevisan & Mendes, 2005;Faria et al, 2017). Ethylene is a Acta Scientiarum.…”
Section: Discussionmentioning
confidence: 99%
“…Although slow growth is considered a promising method for the conservation of germplasm in Passiflora, difficulties in maintaining seed banks and field collections relate to few available studies in the literature focused on developing protocols for passion fruit species (Faria, Costa, Junghans, Ledo, & Souza, 2006;Garcia, Pacheco, Vianna, & Mansur, 2011;Pacheco et al, 2016;Faria et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of silver nitrate and cobalt chloride, known ethylene inhibitors, may have led to a lower accumulation of ethylene in the atmosphere inside the culture test tubes, which stimulated the multiplication of Andrographis paniculata (Das & Bandyopadhyay, 2020). This effect was also raised in the production of Passiflora gibertii (Faria et al, 2017) and Glycyrrhiza glabra (Tahoori et al, 2018). Sarropoulou et al (2016), observed direct effects of silver nitrate, silver sulfate and cobalt chloride on the proliferation of shoots in vitro and on the rooting of cherry.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales ...mentioning
confidence: 99%
“…In this study addition of Ag + ions promoted the flowering induction in rose shoots, but high concentrations resulted in possible toxic effects to flower development. Silver ions acts causing block in ethylene receptors in plants, inhibiting ethylene effects (Santana-Buzzy et al, 2006;Faria et al, 2017). Thus, ethylene may be involved directly or indirectly in inhibiting of the flowering induction in roses.…”
Section: Agno 3 Influenced Induction and Development Of In Vitro Flowmentioning
confidence: 99%